PENGGUNAAN ALGORITMA SIMULATED ANNEALING UNTUK MENYELESAIKAN TEKA-TEKI BINARY DAN SUDOKU ( Solving Binary and Sudoku Puzzles with a Simulated Annealing Algorithm ) - Bagus Sartono (FORUM STATISTIKA DAN KOMPUTASI, 2011)
Binary and Sudoku puzzles could be seen as optimization problems by using a score of rules violation as the objective function which is minimized. The simulated annealing algorithm is a good alternative to solve the puzzles. This paper describes the approach which implements the algorithm and presents the SAS/IML program of it. Empirical trials show that the approach works well to find the solution of the puzzles in a satisfying run time. Keywords : meta-heuristic, simulated annealing